GLOBALISASI, PELAYARAN-PERDAGANGAN DAN DIVERSITAS POPULASI: STUDI SISA MANUSIA SITUS LERAN, REMBANG, JAWA TENGAH - Sofwan Noerwidi (Berkala Arkeologi, 2017)
The issue of globalization is booming recently, but it is not really a new thing in the history of human civilization. However, the issue of globalization in the past, -particularly in Archaeological perspective- is not too much discussed among social sciences in Indonesia. This paper aims to open the isolation by understanding the processes of globalization and its correlation to the maritime trade through archaeological data based on human remains from Leran burial site, Rembang, Central Java. Research method used in this paper is Bioarchaeological approach based on dental metric and non-metric characters analysis which performed to determine the biological affinity of Leran people in comparison with some samples from surrounding area. The result could be seen that the Leran population has a fairly diverse biological affinity which correlated to the strategic position of this site in the ancient global network of maritime trade.